Role of Legionella pneumophila outer membrane vesicles in host-pathogen interaction - Ayesha, Ayesha; Chow, Franklin Wang-Ngai; Leung, Polly Hang-Mei (Frontiers in Microbiology, 2023)
Legionella pneumophila is an opportunistic intracellular pathogen that inhabits artificial water systems and can be transmitted to human hosts by contaminated aerosols. Upon inhalation, it colonizes and grows inside the alveolar macrophages and causes Legionnaires' disease. To effectively control and manage Legionnaires' disease, a deep understanding of the hostpathogen interaction is crucial. Bacterial extracellular vesicles, particularly outer membrane vesicles (OMVs) have emerged as mediators of intercellular communication between bacteria and host cells. These OMVs carry a diverse cargo, including proteins, toxins, virulence factors, and nucleic acids. OMVs play a pivotal role in disease pathogenesis by helping bacteria in colonization, delivering virulence factors into host cells, and modulating host immune responses. This review highlights the role of OMVs in the context of host-pathogen interaction shedding light on the pathogenesis of L. pneumophila. Understanding the functions of OMVs and their cargo provides valuable insights into potential therapeutic targets and interventions for combating Legionnaires' disease.